Pelaksanaan Pembinaan Mental Spiritual Di Panti Sosial DKI Jakarta - Kamarusdiana, Kamarusdiana; Maarif, Syamsul; Ivalaili, Ivalaili (Center of Community Service (PPM), Institute for Research and Community Services (LP2M) UI, 2021)
This study aims to find out the pattern of spiritual mental development in social homes and what factors encourage and inhibit spiritual mental development in social homes by focusing on the pattern of coaching, impact, as well as the driving factors and inhibitions. The approach used is a case study with an evaluative research pattern, as well as analysis of research objects in several social homes for the elderly and children in DKI Jakarta. Data collection using observation methods, interviews, documentation, and library studies. The results of the study found that the spiritual mental development of orphanage residents is carried out through religious practices such as prayers, quran reading in addition to lectures, religious questions and answers, in addition there are spiritual mental coaching programs that are ceremonial such as maulid Nabi, Isra Miraj and Eid al-Adha and Eid al-Fitr prayers. The implementation of spiritual mental development in the orphanage environment has been supported by adequate infrastructure, only the teaching curriculum has not been properly systemized.